Memproduksi Ruang Kota dari Bawah: Praktik Spasial Pengamen Badut Usia Sekolah di Kota Palopo - Muhammad Ashabul Kahfi; Fitriani Jamaluddin (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This study analyzes how school-aged mascot buskers in Palopo City actively produce urban public space into social and economic space through their everyday spatial practices. Urban intersections, shopping districts, minimarket areas, and temporary event spaces are commonly designed for mobility and circulation; however, these spaces are continuously reproduced as informal economic arenas by children who remain formally enrolled in school. While existing research tends to frame working children as victims of economic deprivation, their role as active producers of urban space remains underexplored, particularly in medium-sized Indonesian cities. This study employed a qualitative approach with a socio-spatial case study design, grounded in Henri Lefebvre's triadic theory of the production of space, spatial practice, representations of space, and representational space. Data were collected through non-participant observation, in-depth interviews, and visual documentation involving seven school-aged mascot buskers selected through purposive sampling in Palopo City, South Sulawesi. Findings reveal that the children developed clear mental maps of profitable and socially safe locations, regulated their spatial mobility according to traffic rhythms and peak hours, and negotiated their dual identity as students and informal workers within public space. Urban space was simultaneously experienced as a site of economic survival, social stigma, emotional enjoyment, and peer solidarity. This study contributes to urban sociology and childhood studies by repositioning school-aged child workers as active spatial producers rather than passive victims of poverty, and by extending Lefebvre's theory to the context of children's informal labor in medium-sized Indonesian cities